Antibacterial Activity of Leaf Extracts of Cinnamomum zeylanicum, Camellia sinensis, Lawsonia inermis, and Pistacia atlantica on Bacteria Isolated from Burn Patients - Hana S. Alhadi (المجلة الأفروآسيوية للبحث العلمي, 2024)
Objective: To investigate the antimicrobial activities of Pistacia atlantica, Lawsonia inermis, Camellia sinensis, and Cinnamomum zeylanicum leaf extracts against various bacterial strains at different concentrations. Methods: The study involved testing the leaf extracts of the mentioned plant species at concentrations of 100%, 75%, 50%, and 25% against Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella typhi, and Escherichia coli. The diameter of the zones of inhibition measured the inhibitory effects. Results: At 100% concentration, Camellia sinensis, Cinnamomum zeylanicum, Lawsonia inermis, and Pistacia atlantica exhibited varying degrees of effectiveness against the tested bacterial strains. The efficacy decreased as the concentration reduced: 75% > 50% > 25%. The lowest concentration of 25% showed the least impact on the bacterial isolates. Conclusion: The results demonstrate that higher concentrations of the plant extracts showed greater antimicrobial efficacy against the bacterial strains studied. This suggests that these natural extracts could be potential alternatives in combating infections caused by multidrug-resistant bacteria. Further research is warranted to explore the full potential of these plant-derived compounds in addressing the challenges posed by antibiotic-resistant microorganisms.